(untitled) (Revista Tempo e Argumento, 2019)
This article aims at exploring theoretical possibilities that allow us to discuss the political narrative of Brazilian democratization, a process usually situated from 1974 onwards, when a so-called political distension was announced by the military dictatorship. A narrative constructed by the big press, which emerged as one of the privileged democratization voices, this established the prominence of certain political and social players and sectors. The study focus lies on the newspaper Folha de S. Paulo, whose pages provided a prominent place for the negotiations involving the Brazilian political system and the appreciation of elections as a way of institutionalizing the regime. Keywords: Redemocratization. Dictatorship. Big Press. Political Relations. Narrative.